Respuesta :

Answer:

a² - 7a + 10

Step-by-step explanation:

Substitute all x variables for (2 - a) and evaluate.

[tex](2-a)^2+3(2-a)\\\\(2-a)(2-a)+3(2-a)\\\\4-2a-2a+a^2+6-3a\\\\a^2-7a+10[/tex]

[tex]option \: (b)[/tex]

Step-by-step explanation:-

[tex]f(x) = {x}^{2} + 3x[/tex]

[tex]put \: x = (2 - a)[/tex]

[tex]f(x) = {(2 - a)}^{2} + 3(2 - a)[/tex]

Apply (a-b)² formula for (2-a)².

[tex] {(a - b)}^{2} = {a}^{2} + {b}^{2} - 2ab [/tex]

[tex]f(x) = {2}^{2} + {a}^{2} - 2(2a) + 3(2 - a)[/tex]

[tex]f(x) = 4 + {a}^{2} - 4a + 6 - 3a[/tex]

[tex]f(x) = 4 + {a}^{2} - 7a + 6[/tex]

[tex]f(x) = {a}^{2} - 7a + 6 + 4[/tex]

[tex]f(x) = {a}^{2} - 7a + 10.[/tex]

Hence, option (b) is correct.

ACCESS MORE